Effectiveness of piperonyl butoxide and pyrethroid-treated long-lasting insecticidal nets (LLINs) versus pyrethroid-only LLINs with and without indoor residual spray against malaria infection: third year results of a cluster, randomised controlled, two-by-two factorial design trial in Tanzania - Natacha Protopopoff; Jacklin F. Mosha; Louisa A. Messenger; Eliud Lukole; Jacques D. Charlwood; Alexandra Wright; Enock Kessy; Alphaxard Manjurano; Franklin W. Mosha; Immo Kleinschmidt; Mark Rowland (Malaria Journal, 2023)
Abstract Background After decades of success in reducing malaria through the scale-up of pyrethroid long-lasting insecticidal nets (LLINs), the decline in the malaria burden has stalled, coinciding with the rapid spread of pyrethroid resistance. In a previously reported study, nets treated with a pyrethroid and a synergist, piperonyl butoxide (PBO), demonstrated superior efficacy compared to standard pyrethroid LLINs (std-LLINs) against malaria. Evidence was used to support the public health recommendation of PBO-Pyrethroid-LLIN by the World Health Organization in 2018. This study looks at the third year of rollout of these nets in Muleba district, Tanzania to inform whether policy guidelines need to be updated. Methods A four-group cluster randomized trial (CRT) using a two-by-two factorial design was carried out between January 2014 and December 2017. A total of 48 clusters, were randomized in a 1:1:1:1 ratio to the following treatment groups, each intervention being provided once in 2015: 1/std-LLIN; 2/PBO-pyrethroid LLIN; 3/std-LLIN + Indoor Residual Spraying (IRS) and 4/PBO-Pyrethroid-LLIN + IRS. During the third year follow-up, malaria infection prevalence in 80 children per cluster, aged 6 months to 14 years, was measured at 28- and 33-months post-intervention and analysed as intention-to-treat (ITT) and per protocol (PP). Mosquito collections were performed monthly in all clusters, using CDC light traps in 7 randomly selected houses per cluster. Results At 28 and 33 months, study net usage among household participants was only 47% and 31%, respectively. In ITT analysis, after 28 months malaria infection prevalence among 7471 children was 80.9% in the two std-LLIN groups compared to 69.3% in the two PBO-Pyrethroid-LLIN (Odds Ratio: 0.45, 95% Confidence Interval: 0.21–0.95, p-value: 0.0364). After 33 months the effect was weaker in the ITT analysis (prevalence 59.6% versus 49.9%, OR: 0.60, 95%CI:0.32–1.13, p-value: 0.1131) but still evident in the PP analysis (57.2% versus 44.2%, OR: 0.34, 95%CI: 0.16–0.71, p-value: 0.0051). Mean number of Anopheles per night collected per house was similar between PBO-Pyrethroid-LLIN groups (5.48) and std-LLIN groups (5.24) during the third year. Conclusions Despite low usage of PBO- Pyrethroid LLIN, a small impact of those nets on malaria infection prevalence was still observed in the 3rd year with the most protection offered to children still using them. To maximize impact, it is essential that net re-distribution cycles are aligned with this LLIN lifespan to maintain maximum coverage. Trial registration: The trial was registered with ClinicalTrials.gov (registration number NCT02288637).